Architectural agents : the delusional, abusive, addictive lives of buildings - Wharton, Annabel Jane (University of Minnesota Press, 2016)
Buildings are not benign; rather, they commonly manipulate and abuse their human users. 'Architectural Agents' makes the case that buildings act in the world independently of their makers, patrons, owners, or occupants. And often they act badly. Treating buildings as bodies, Annabel Jane Wharton writes biographies of symptomatic structures in order to diagnose their pathologies.